Dataset on the thermal performance of green roofs and green walls in a temperate continental climate: An experimental approach in Quito, EcuadorMendeley Data - Marcelo Villacis-Ormaza (Data in Brief)
This dataset comprises temperature and humidity measurements obtained from two experimental building prototypes designed to characterize the thermal behavior of green roofs and green walls in a temperate continental climate. The data was collected at an elevation of 2850 m above sea level in Quito, Ecuador (−0.120694, −78.498677). At 15-min intervals, calibrated digital sensors recorded the temperature and relative humidity indoors over the course of four months. Values from two configurations are included in the dataset: one that integrates green infrastructure and another that acts as a base case devoid of vegetation. With possible uses for building simulations, urban climate studies, and policy creation, the data are organized to promote study on thermal comfort, energy efficiency, and sustainable construction methods.